Prognostic impact of interstitial lung abnormalities in lung cancer: a systematic review and meta-analysis - Tang, Xian-Liang; Sun, Yin-Bo; Guo, Xiao-Tong; Yang, Sheng-Zhao; Zhang, Wen-Ping (Frontiers in Oncology, 2024)
Background Newly identified as a radiological concept, interstitial lung abnormalities (ILA) is emerging as a prognostic factor for lung cancer. Yet, debates persist regarding the prognostic significance of ILA in lung cancer. Our inaugural meta-analysis aimed to investigate the correlation between ILA and lung cancer outcomes, offering additional insights for clinicians in predicting patient prognosis. Methods Articles meeting the criteria were found through PubMed, the Cochrane Library, EMBASE, and Web of Science by February 29, 2024. The outcomes evaluated were the survival rates such as overall survival (OS), disease-free survival (DFS), progression-free survival (PFS), and cancer-specific survival (CSS). Results A total of 12 articles with 4416 patients were included in this meta-analysis. The pooled results showed that lung cancer patients with interstitial lung abnormalities had an inferior OS (n=11; HR=2.22; 95% CI=1.68-2.95; P<0.001; I2 = 72.0%; Ph<0.001), PFS (n=3; HR=1.59; 95% CI=1.08-2.32; P=0.017; I2 = 0%; Ph=0.772), and CSS (n=2; HR=4.00; 95% CI=1.94-8.25; P<0.001; I2 = 0%; Ph=0.594) than those without, however, the ILA was not significantly associated with the DFS (n=2; HR=2.07; 95% CI=0.94-7.02; P=0.066; I2 = 90.4%; Ph=0.001). Moreover, lung cancer patients with ILA were significantly correlated with male (OR=2.43; 95% CI=1.48-3.98; P<0.001), smoking history (OR=2.11; 95% CI=1.37-3.25; P<0.001), advanced age (OR=2.50; 95% CI=1.56-4.03; P<0.001), squamous carcinoma (OR=0.42; 95% CI=0.24-0.71; P=0.01), and EGFR mutation (OR=0.50; 95% CI=0.32-0.78; P=0.002). The correlation between ILA and race, stage, ALK, however, was not significant. Conclusion ILA was a availability factors of prognosis in patients with lung cancers. These findings highlight the importance of early pulmonary fibrosis, namely ILA for prognosis in patients with lung cancer, and provide a partial rationale for future clinical work.